Iron at the interface of immunity and infection - Nairz, Manfred; Haschka, David; Demetz, Egon; Weiss, Günter (Frontiers in Pharmacology, 2014)
Both, mammalian cells and microbes have an essential need for iron, which is required for many metabolic processes and for microbial pathogenicity. In addition, cross-regulatory interactions between iron homeostasis and immune function are evident. Cytokines and the acute phase protein hepcidin affect iron homeostasis leading to the retention of the metal within macrophages and hypoferremia. This is considered to result from a defense mechanism of the body to limit the availability of iron for extracellular pathogens while on the other hand the reduction of circulating iron results in the development of anemia of inflammation. Opposite, iron and the erythropoiesis inducing hormone erythropoietin affect innate immune responses by influencing IFN- mediated (iron) or NF-kB inducible (erythropoietin) immune effector pathways in macrophages. Thus, macrophages loaded with iron lose their ability to kill intracellular pathogens via IFN- mediated effector pathways such as nitric oxide (NO) formation. Accordingly, macrophages invaded by the intracellular bacteria Salmonella enterica serovar Typhimurium increase the expression of the iron export protein ferroportin thereby reducing the availability of iron for intramacrophage bacteria while on the other side strengthening anti-microbial macrophage effector pathways via increased formation of NO or TNF-. In addition, certain innate resistance genes such as natural resistance associated macrophage protein function (Nramp1) or lipocalin-2 exert part of their antimicrobial activity by controlling host and/or microbial iron homeostasis. Consequently, pharmacological or dietary modification of cellular iron trafficking enhances host resistance to intracellular pathogens but may increase susceptibility to microbes in the extracellular compartment and vice versa. Thus, the control over iron homeostasis is a central battlefield in host-pathogen interplay influencing the course of an infectious disease.